Congenital pancreatic pseudocyst - Jia Shi; Chengdong Wang; Fan Lv (Journal of Pediatric Surgery Case Reports, 2020)
Pancreatic pseudocysts (PPs) rarely occur in the fetus. Accurate prenatal diagnosis is challenging. We report a case of left upper abdominal cystic mass detected by prenatal ultrasonography and Magnetic resonance imaging (MRI), which finally proven PPs histologically after birth. Operative interventions include complete pseudocystectomy and subsequent external drainage. The outcome is satisfactory. Keywords: Pancreatic pseudocyst, Congenital, Treatment